Desempenho na linguagem receptiva e expressiva de crianças com síndrome de Down - Brandão, Sílvia Regina Silva (2006)
This research aimed at verifying the performance in receptive and expressive language of ten Pre- School Portuguese speaking children with Down Syndrome (DS), compared with twenty children with typical development. The two groups were equalized by their development age attempting at investigating the doubts raised by the literature about DS children language acquisition. The PEP-R (Leon, 2002) evaluation instrument which verifies both general and specific development and provides information on the emerging abilities was used. The areas of Imitation, Perception, Fine Motor, Gross Motor, Visual-Motor, Language Comprehension and Expression were evaluated to verify the relationship of the five first areas with the last two areas. Additionally, four dimensions of the Behavior Scale were evaluated: relations and affect; playing and interest for materials; sensory responses and language. We made comparisons amongst the study group (SG), the control group (CG) and, the DS children. Children of the SG were compared to their corresponding pairs of the CG, which had the same developmental age. Results concerning the SG indicate that while Language Comprehension presents levels similar to Developing Age and lower to those of Chronological Age, the Language Expression stands out with more delay than one could expect. The delay in the acquisition of language production abilities points out as an important characteristic in language problems. The shortage in Expressive Language is significantly greater than global shortage in SG. Children in CG show an harmonic development profile while, SG show a decreasing profile with higher Chronological Age, followed by Development Age, Language Comprehension and last of all the Language Expression. In the SG, the Area of Language Comprehension is correlated to the area of Perception, Fine Motor and Visual Motor while, the Area of Language Expression is associated only to the area of Imitation. The use of pronouns and syntactic abilities were the most affected aspects. Lexical abilities are less implicated than grammatical ones. We conclude that the language production disorders are an important feature of language deficits in DS. Deficits of expressive language are significantly greater in relation to the global delay. We observed the existence of different development characteristics between SG and CG with an asynchrony between the Areas of Language Comprehension and Expression and the Areas of Expressive and Emerging Abilities. The apparent absence of a linkage between language reception and production, suggests that the Area of Language Expression may function as an independent module. It is than discarded any possibility that Down Syndrome Children could present a similar development, only slower than those of children without DS. Regarding to the comprehension abilities of the SG, it seems initially to develop parallel to cognitive abilities but, it gradually becomes lower than child global development abilities. There were evidences that differences in the development of Language Expression become higher as the child chronological age increases. Besides the cognitive and language disorders, the individuals with DS present significant articulatory problems which contribute to the intelligibility of their speech. The emergent abilities scores may represent adequate indexes to future prognostic of language development in DS children to be confirmed by longitudinal studies.